1992
DOI: 10.1007/bf01458105
|View full text |Cite
|
Sign up to set email alerts
|

A time-limited group therapy model for men sexually abused as children

Abstract: This article will provide an overview of male child sexual abuse victims and the traumatic consequences it inflicts upon their later adult development. A group treatment model is presented for adult males who experienced sexual abuse in their childhood. Although group therapy is frequently advocated for women survivors (Brandt, 1989;Douglas & Matson, 1989), little clinical evidence exists which supports its use among men. A group experience for these men, however, is a beneficial therapeutic adjunct to individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
(45 reference statements)
0
3
0
1
Order By: Relevance
“…While preventing CSA before it occurs is the single most effective way to shield a child from its adverse impacts, researchers agree that the timely disclosure of CSA is imperative to buffering the long‐term negative sequalae of CSA once it has occurred (Kendall‐Tackett, Williams, & Finkelhor, 1993; Kogan, 2004; Wager et al, 2015). Though largely dependent on the reaction received upon CSA disclosure and the overall quality of the victim's support structure (e.g., Ahrens, 2006; Ahrens, Cabral, & Abeling, 2009), research has shown that CSA disclosure can be of value for the victim's adaptive psychosocial development, in that it can help the child understand the abuse, manage feelings of abandonment or anger, and develop a sense of hope and trust in healthy interpersonal relationships (Isely, 1992; Lamb & Edgar‐Smith, 1994; Park & Blumberg, 2002; Pipe et al, 2007). To this end, it is not surprising that children who disclose their adverse experiences in a timely fashion tend to demonstrate fewer adverse psychological sequalae and problem behaviors post‐abuse than those who delay their disclosure or do not disclose at all (Broman‐Fulks et al, 2007; Townsend, 2016; Ullman, 2007).…”
Section: Disclosure Of Csamentioning
confidence: 99%
“…While preventing CSA before it occurs is the single most effective way to shield a child from its adverse impacts, researchers agree that the timely disclosure of CSA is imperative to buffering the long‐term negative sequalae of CSA once it has occurred (Kendall‐Tackett, Williams, & Finkelhor, 1993; Kogan, 2004; Wager et al, 2015). Though largely dependent on the reaction received upon CSA disclosure and the overall quality of the victim's support structure (e.g., Ahrens, 2006; Ahrens, Cabral, & Abeling, 2009), research has shown that CSA disclosure can be of value for the victim's adaptive psychosocial development, in that it can help the child understand the abuse, manage feelings of abandonment or anger, and develop a sense of hope and trust in healthy interpersonal relationships (Isely, 1992; Lamb & Edgar‐Smith, 1994; Park & Blumberg, 2002; Pipe et al, 2007). To this end, it is not surprising that children who disclose their adverse experiences in a timely fashion tend to demonstrate fewer adverse psychological sequalae and problem behaviors post‐abuse than those who delay their disclosure or do not disclose at all (Broman‐Fulks et al, 2007; Townsend, 2016; Ullman, 2007).…”
Section: Disclosure Of Csamentioning
confidence: 99%
“…For a description and statement of purpose of short-and long-term groups for incest survivors, see Blake- White and Kline (1985), Cahill et al (1991), and Goodwin and Talwar (1989). Some studies suggest that group treatment for adult male survivors should address unique issues relevant to men, such as the discordant images of stereotypically male attributes and those associated with victims of child sexual abuse (Isely, 1982). In general, self-help groups focus on decreasing shame and guilt and on increasing support, coping strategies, and incest knowledge.…”
Section: Treatment For Adults Abused As Childrenmentioning
confidence: 99%
“…This difficult task can be made easier if the groundwork during the initial phases of therapy has been done well. Isely (1992) maintained that the expression of aggression by male victims masks "painful feelings of aban'donment, grief, and the desire to experience vulnerability within the [therapy] group. .…”
Section: Strategies For Interventionmentioning
confidence: 97%